2013
DOI: 10.1017/s1461145712000016
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of synapse and glutamate related genes in post-mortem hippocampus of depressed subjects

Abstract: Major depressive disorder (MDD) has been linked to changes in function and activity of the hippocampus, one of the central limbic regions involved in regulation of emotions and mood. The exact cellular and molecular mechanisms underlying hippocampal plasticity in response to stress are yet to be fully characterized. In this study, we examined the genetic profile of micro-dissected subfields of post-mortem hippocampus from subjects diagnosed with MDD and comparison subjects matched for sex, race and age. Gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(161 citation statements)
references
References 78 publications
7
153
0
1
Order By: Relevance
“…22 In addition, ketamine treatment in rats can lead to upregulation of AMPAR subunit (GluA1 and GluA2) total or surface expres sion in the PFC and hippocampus, as measured by Western blot 22,33,40,41 or by surface biotinylation assays, 39 along with in creased hippocampal AMPAR binding, as measured by auto radiography. 42 Interestingly, postmortem studies have re ported reductions in the mRNA expression levels of AMPA receptor subunits GluA1 and GluA3 in the perirhinal cortex, CA1 and dentate gyrus 44 of patients with depression, and several animal studies similarly found that exposure to chronic stress leads to a decrease in the expression of AMPAR subunits in these brain regions. [44][45][46] Sitespecific AMPAR phosphorylation at serine, threonine or tyrosine resi dues in the intracellular Cterminal domain by various protein kinases is known to modulate the channel kinetics, localization, subunit composition and protein-protein inter actions of AMPARs.…”
Section: Role Of Ampa Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In addition, ketamine treatment in rats can lead to upregulation of AMPAR subunit (GluA1 and GluA2) total or surface expres sion in the PFC and hippocampus, as measured by Western blot 22,33,40,41 or by surface biotinylation assays, 39 along with in creased hippocampal AMPAR binding, as measured by auto radiography. 42 Interestingly, postmortem studies have re ported reductions in the mRNA expression levels of AMPA receptor subunits GluA1 and GluA3 in the perirhinal cortex, CA1 and dentate gyrus 44 of patients with depression, and several animal studies similarly found that exposure to chronic stress leads to a decrease in the expression of AMPAR subunits in these brain regions. [44][45][46] Sitespecific AMPAR phosphorylation at serine, threonine or tyrosine resi dues in the intracellular Cterminal domain by various protein kinases is known to modulate the channel kinetics, localization, subunit composition and protein-protein inter actions of AMPARs.…”
Section: Role Of Ampa Receptorsmentioning
confidence: 99%
“…42 Interestingly, postmortem studies have re ported reductions in the mRNA expression levels of AMPA receptor subunits GluA1 and GluA3 in the perirhinal cortex, CA1 and dentate gyrus 44 of patients with depression, and several animal studies similarly found that exposure to chronic stress leads to a decrease in the expression of AMPAR subunits in these brain regions. [44][45][46] Sitespecific AMPAR phosphorylation at serine, threonine or tyrosine resi dues in the intracellular Cterminal domain by various protein kinases is known to modulate the channel kinetics, localization, subunit composition and protein-protein inter actions of AMPARs. 28 In addition to regulating the number of AMPA receptors on the surface, ketamine has been shown to affect the phosphorylation state of AMPAR subunits.…”
Section: Role Of Ampa Receptorsmentioning
confidence: 99%
“…Brain tissue was collected as previously described from MDD and psychiatrically healthy matched subjects (Duric et al, 2013;Kang et al, 2007;Sibille et al, 2011). Informed consent was obtained from the next of kin for all subjects, and all procedures were approved by the University of Pittsburgh's Committee for the Oversight of Research Involving the Dead and Institutional Review Board for Biomedical Research, or by the Institutional Review Board of the University Hospitals of Cleveland.…”
Section: Human Subjectsmentioning
confidence: 99%
“…Glutamatergic pathways could also contribute to hippocampal changes in persons with MDD. Dysregulation of genes involved in glutamatemediated neuronal and synaptic plasticity has been reported in postmortem hippocampal slices from depressed patients (Duric et al, 2013). Genetic factors may also have a role.…”
Section: Introductionmentioning
confidence: 99%